Hypervalent iodine compounds for anti-Markovnikov-type iodo-oxyimidation of vinylarenes - Krylov, Igor B.; Paveliev, Stanislav A.; Syroeshkin, Mikhail A.; Korlyukov, Alexander A.; Dorovatovskii, Pavel V.; Zubavichus, Yan V.; Nikishin, Gennady I.; Terent’ev, Alexander O. (Beilstein Journal of Organic Chemistry, 2018)
The iodo-oxyimidation of styrenes with the N-hydroxyimide/I2/hypervalent iodine oxidant system was proposed. Among the examined hypervalent iodine oxidants (PIDA, PIFA, IBX, DMP) PhI(OAc)2 proved to be the most effective; yields of iodo-oxyimides are 34–91%. A plausible reaction pathway includes the addition of an imide-N-oxyl radical to the double C=C bond and trapping of the resultant benzylic radical by iodine. It was shown that the iodine atom in the prepared iodo-oxyimides can be substituted by various nucleophiles.
Keywords: free radicals; hypervalent iodine; imide-N-oxyl radicals; iodination; N-hydroxyimides; oxidative functionalization

(untitled) - Hicks, R. G. (Org. Biomol. Chem., 2007)

(untitled) - Mas-Torrent, M.; Crivillers, N.; Rovira, C.; Veciana, J. (Chem. Rev., 2012)

Nitroxides - Theory, Experiment and Applications - Berliner, L. J. (History of the Use of Nitroxides (Aminoxyl Radicals) in Biochemistry: Past, Present and Future of Spin Label and Probe Method, 2012)

(untitled) - Tretyakov, E. V.; Ovcharenko, V. I. (Russ. Chem. Rev., 2009)

(untitled) - Train, C.; Norel, L.; Baumgarten, M. (Coord. Chem. Rev., 2009)

(untitled) - Sugawara, T.; Komatsu, H.; Suzuki, K. (Chem. Soc. Rev., 2011)

(untitled) - Suzuki, K.; Uchida, Y.; Tamura, R.; Shimono, S.; Yamauchi, J. (J. Mater. Chem., 2012)

(untitled) - Uchida, Y.; Suzuki, K.; Tamura, R. (J. Phys. Chem. B, 2012)

(untitled) - Suga, T.; Konishi, H.; Nishide, H. (Chem. Commun., 2007)

(untitled) - Hawker, C. J.; Bosman, A. W.; Harth, E. (Chem. Rev., 2001)

(untitled) - Tebben, L.; Studer, A. (Angew. Chem., Int. Ed., 2011)

(untitled) - Bagryanskaya, E. G.; Marque, S. R. A. (Chem. Rev., 2014)

(untitled) - Ciriminna, R.; Pagliaro, M. (Org. Process Res. Dev., 2010)

(untitled) - Hamada, S.; Furuta, T.; Wada, Y.; Kawabata, T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Ryland, B. L.; Stahl, S. S. (Angew. Chem., Int. Ed., 2014)

(untitled) - Wertz, S.; Studer, A. (Green Chem., 2013)

(untitled) - Muramatsu, W.; Nakano, K. (Org. Lett., 2015)

(untitled) - Recupero, F.; Punta, C. (Chem. Rev., 2007)

(untitled) - Galli, C.; Gentili, P.; Lanzalunga, O. (Angew. Chem., Int. Ed., 2008)

(untitled) - Wentzel, B. B.; Donners, M. P. J.; Alsters, P. L.; Feiters, M. C.; Nolte, R. J. M. (Tetrahedron, 2000)

(untitled) - Amaoka, Y.; Kamijo, S.; Hoshikawa, T.; Inoue, M. (J. Org. Chem., 2012)

(untitled) - Sakaguchi, S.; Hirabayashi, T.; Ishii, Y. (Chem. Commun., 2002)

(untitled) - Sakaguchi, S.; Eikawa, M.; Ishii, Y. (Tetrahedron Lett., 1997)

(untitled) - Ishii, Y.; Iwahama, T.; Sakaguchi, S.; Nakayama, K.; Nishiyama, Y. (J. Org. Chem., 1996)

(untitled) - Minisci, F.; Punta, C.; Recupero, F. (J. Mol. Catal. A: Chem., 2006)

(untitled) - Lee, J. M.; Park, E. J.; Cho, S. H.; Chang, S. (J. Am. Chem. Soc., 2008)

(untitled) - Terent'ev, A. O.; Krylov, I. B.; Sharipov, M. Y.; Kazanskaya, Z. M.; Nikishin, G. I. (Tetrahedron, 2012)

(untitled) - Terent'ev, A. O.; Krylov, I. B.; Timofeev, V. P.; Starikova, Z. A.; Merkulova, V. M.; Ilovaisky, A. I.; Nikishin, G. I. (Adv. Synth. Catal., 2013)

(untitled) - Krylov, I. B.; Vil', V. A.; Terent'ev, A. O. (Beilstein J. Org. Chem., 2015)

(untitled) - Ananikov, V. P.; Eremin, D. B.; Yakukhnov, S. A.; Dilman, A. D.; Levin, V. V.; Egorov, M. P.; Karlov, S. S.; Kustov, L. M.; Tarasov, A. L.; Greish, A. A.; Shesterkina, A. A.; Sakharov, A. M.; et al. (Mendeleev Commun., 2017)

(untitled) - Krylov, I. B.; Paveliev, S. A.; Shelimov, B. N.; Lokshin, B. V.; Garbuzova, I. A.; Tafeenko, V. A.; Chernyshev, V. V.; Budnikov, A. S.; Nikishin, G. I.; Terent'ev, A. O. (Org. Chem. Front., 2017)

(untitled) - Guo, Z.; Jin, C.; Zhou, J.; Su, W. (RSC Adv., 2016)

(untitled) - Lv, Y.; Sun, K.; Wang, T.; Li, G.; Pu, W.; Chai, N.; Shen, H.; Wu, Y. (RSC Adv., 2015)

(untitled) - Qian, P.-C.; Liu, Y.; Song, R.-J.; Hu, M.; Yang, X.-H.; Xiang, J.-N.; Li, J.-H. (Eur. J. Org. Chem., 2015)

(untitled) - Dian, L.; Wang, S.; Zhang-Negrerie, D.; Du, Y. (Adv. Synth. Catal., 2015)

(untitled) - Dinda, M.; Bose, C.; Ghosh, T.; Maity, S. (RSC Adv., 2015)

(untitled) - Guo, Z.; Jiang, X.; Jin, C.; Zhou, J.; Sun, B.; Su, W. (Synlett, 2017)

(untitled) - Lv, Y.; Sun, K.; Pu, W.; Mao, S.; Li, G.; Niu, J.; Chen, Q.; Wang, T. (RSC Adv., 2016)

(untitled) - Tan, B.; Toda, N.; Barbas, C. F., III (Angew. Chem., Int. Ed., 2012)

(untitled) - Xu, X.; Li, P.; Huang, Y.; Tong, C.; Yan, Y.; Xie, Y. (Tetrahedron Lett., 2017)

(untitled) - Xu, X.; Sun, J.; Lin, Y.; Cheng, J.; Li, P.; Yan, Y.; Shuai, Q.; Xie, Y. (Org. Biomol. Chem., 2017)

(untitled) - Siddaraju, Y.; Prabhu, K. R. (Org. Biomol. Chem., 2015)

(untitled) - Kompanets, M. O.; Kushch, O. V.; Litvinov, Y. E.; Pliekhov, O. L.; Novikova, K. V.; Novokhatko, A. O.; Shendrik, A. N.; Vasilyev, A. V.; Opeida, I. O. (Catal. Commun., 2014)

(untitled) - Kasperczyk, K.; Orlińska, B.; Zawadiak, J. (Cent. Eur. J. Chem., 2014)

(untitled) - Bag, R.; De, P. B.; Pradhan, S.; Punniyamurthy, T. (Eur. J. Org. Chem., 2017)

(untitled) - Xia, X.-F.; Zhu, S.-L.; Hu, Q.-T.; Chen, C. (Tetrahedron, 2016)

(untitled) - Bag, R.; Sar, D.; Punniyamurthy, T. (Org. Biomol. Chem., 2016)

(untitled) - Yamamoto, D.; Soga, M.; Ansai, H.; Makino, K. (Org. Chem. Front., 2016)

(untitled) - Luo, J.; Zhang, J. (J. Org. Chem., 2016)

(untitled) - Samanta, S.; Ravi, C.; Joshi, A.; Pappula, V.; Adimurthy, S. (Tetrahedron Lett., 2017)

(untitled) - Xia, X.-F.; Zhu, S.-L.; Gu, Z.; Wang, H.; Li, W.; Liu, X.; Liang, Y.-M. (J. Org. Chem., 2015)

(untitled) - Bag, R.; Sar, D.; Punniyamurthy, T. (Org. Lett., 2015)

(untitled) - Andia, A. A.; Miner, M. R.; Woerpel, K. A. (Org. Lett., 2015)

(untitled) - Zhang, J.-Z.; Tang, Y. (Adv. Synth. Catal., 2016)

(untitled) - Samanta, S.; Donthiri, R. R.; Ravi, C.; Adimurthy, S. (J. Org. Chem., 2016)

(untitled) - Huang, L.; Zheng, S.-C.; Tan, B.; Liu, X.-Y. (Org. Lett., 2015)

(untitled) - Li, Y.-X.; Wang, Q.-Q.; Yang, L. (Org. Biomol. Chem., 2017)

(untitled) - Li, Y.; Zhou, X.; Zheng, G.; Zhang, Q. (Beilstein J. Org. Chem., 2015)

(untitled) - Xia, X.-F.; Gu, Z.; Liu, W.; Wang, H.; Xia, Y.; Gao, H.; Liu, X.; Liang, Y.-M. (J. Org. Chem., 2015)

Science of Synthesis Knowledge Updates: 2015/2 - Wirth, T.; Singh, F. V. (Synthesis by substitution of other halogens, 2015)

(untitled) - Myint, Y. Y.; Pasha, M. A. (Synth. Commun., 2004)

(untitled) - Sanseverino, A. M.; de Mattos, M. C. S. (Synthesis, 1998)

(untitled) - Courtneidge, J. L.; Lusztyk, J.; Pagé, D. (Tetrahedron Lett., 1994)

(untitled) - Achar, T. K.; Maiti, S.; Mal, P. (Org. Biomol. Chem., 2016)

(untitled) - Gottam, H.; Vinod, T. K. (J. Org. Chem., 2011)

(untitled) - Moorthy, J. N.; Senapati, K.; Kumar, S. (J. Org. Chem., 2009)

(untitled) - Yusubov, M. S.; Drygunova, L. A.; Zhdankin, V. V. (Synthesis, 2004)

(untitled) - Yusubov, M. S.; Yusubova, R. J.; Filimonov, V. D.; Chi, K.-W. (Synth. Commun., 2004)

(untitled) - Yusubov, M. S.; Yusubova, R. Y.; Filimonov, V. D.; Chi, K.-W. (Russ. J. Org. Chem., 2002)

(untitled) - De Corso, A. R.; Panunzi, B.; Tingoli, M. (Tetrahedron Lett., 2001)

(untitled) - Hokamp, T.; Storm, A. T.; Yusubov, M.; Wirth, T. (Synlett, 2018)

(untitled) - Terent’ev, A. O.; Krylov, I. B.; Borisov, D. A.; Nikishin, G. I. (Synthesis, 2007)

(untitled) - Terent’ev, A. O.; Borisov, A. M.; Platonov, M. M.; Starikova, Z. A.; Chernyshev, V. V.; Nikishin, G. I. (Synthesis, 2009)

(untitled) - Wu, X.-F.; Gong, J.-L.; Qi, X. (Org. Biomol. Chem., 2014)

(untitled) - Thottumkara, A. P.; Bowsher, M. S.; Vinod, T. K. (Org. Lett., 2005)

(untitled) - Xia, X.-F.; Zhu, S.-L.; Zhang, D. (Tetrahedron, 2015)

(untitled) - Krylov, I. B.; Kompanets, M. O.; Novikova, K. V.; Opeida, I. O.; Kushch, O. V.; Shelimov, B. N.; Nikishin, G. I.; Levitsky, D. O.; Terent'ev, A. O. (J. Phys. Chem. A, 2016)

(untitled) - Rafiee, M.; Wang, F.; Hruszkewycz, D. P.; Stahl, S. S. (J. Am. Chem. Soc., 2018)

(untitled) - Nair, V.; Augustine, A.; George, T. G.; Nair, L. G. (Tetrahedron Lett., 2001)

Organic Electrochemistry, Fifth Edition: Revised and Expanded - Jörissen, J.; Speiser, B. (Preparative Electrolysis on the Laboratory Scale, 2015)